2013
DOI: 10.1103/physreve.87.042303
|View full text |Cite
|
Sign up to set email alerts
|

Amplifying and attenuating the coffee-ring effect in drying sessile nanofluid droplets

Abstract: Experiments and simulations to promote or attenuate the "coffee-ring effect" for pinned sessile nanofluid droplets are presented. The addition of surfactant inside a water suspension of aluminum oxide nanoparticles results in coffee-ring formation after the pinned sessile droplets are fully dried on a substrate, while droplets of the same suspension without the surfactant produce a fine uniform coverage. A mathematical model based on diffusion-limited cluster-cluster aggregation has been developed to explain t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 19 publications
3
48
0
Order By: Relevance
“…[21][22][23][24][25][26][27] More specifically, Still et al 22 achieved a uniform deposition of colloidal particles on glass by adding Sodium dodecyl sulfate (SDS) to the drop dispersion.…”
Section: -12mentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23][24][25][26][27] More specifically, Still et al 22 achieved a uniform deposition of colloidal particles on glass by adding Sodium dodecyl sulfate (SDS) to the drop dispersion.…”
Section: -12mentioning
confidence: 99%
“…However, Crivoi and Duan 25,26 have shown that the formation of coffee ring of graphite nanoparticles is enhanced with the addition of Cetyltrimethyl Ammonium Bromide (CTAB)…”
Section: Sempels Et Almentioning
confidence: 99%
“…Crivoi and Duan studied the effect of hexadecyltrimethylammonium bromide on the deposit morphology obtained by evaporating droplets of dispersed aluminium oxide nanoparticles on Si wafers 31. In the surfactant‐free dispersions, particles tended to aggregate into clusters, which upon drying deposited into a uniform layer enclosed by a visible ring.…”
Section: Interactions Of Particles With/at Interfaces Affecting Thmentioning
confidence: 99%
“…By varying the particle sticking probability from 0 to 100 %, a continuous transformation from a coffee ring to a uniform pattern was observed in the simulations. Therefore, controlling the particle sticking probability by modifying the fluid properties (in this case by the addition of surfactants) offered a way to manipulate the self‐assembly patterns formed from evaporating drops 31…”
Section: Interactions Of Particles With/at Interfaces Affecting Thmentioning
confidence: 99%
“…This highly nonuniform deposition is known as the coffee‐ring effect; it is produced when the drop edges are pinned during evaporation and subsequent radial capillary flows from the drop center carry suspended solutes to the drop perimeter . The coffee‐ring effect, however, can be ameliorated in aqueous systems of large (>10 μm) suspended spheres, in suspensions of ellipsoidal particles with strong capillary interactions, via electrowetting, in systems with strong attractive forces between particles and substrate, and in the presence of surfactants that lead to strong Marangoni flows, among other techniques . In these cases, the drying drop system provides experimenters with an opportunity to make uniform thin particle coatings and films.…”
Section: Introductionmentioning
confidence: 99%